MORAL PHILOSOPHY AND THE DARWINIAN PROBLEM OF SOCIAL EVOLUTION - Yakubu, Yussif (My University, 2015)
Social behaviour is common in nature. Yet, for over a century and half, scholars have struggled in vain to offer a satisfactory account of its evolution under Darwinian natural selection. In this thesis I propose that three fundamental assumptions in the Darwinian explanation of social behaviour are at the root of the problem. They are: 1. The basic Darwinian philosophy that evolutionary change occurs by one inherent trait replacing another in an organism. 2. The collapse of social behaviour, in its entirety, into a single, narrow concept called “altruism.” 3. The assumption that such “altruism” arises from a mutation at a single gene locus, where it supplants “selfishness” as an alternative allele. The thesis identifies some insights from Hume’s analysis of human morality and sociality that suggest the proper circumstances of social interactions in humans. We see from Hume’s analysis that nothing inherent in human nature needs to change in order to move beyond parenting to sociality. Hume identifies two principles in human nature — selfishness and empathy — that are the ultimate basis of human sociality. Empathy expands self-interest to include relatives and associates, but not strangers. And that suffices to form small, primitive human societies. For large, cosmopolitan societies, Hume suggests they are maintained only through human inventions such as governments and justice. Hume’s explanation precludes the need for a weaker “altruistic gene” to supplant a fitter “selfish gene” as a condition for social evolution, which has been the basis of the Darwinian explanatory difficulty.
Keywords: Social Evolution; Moral Philosophy, Darwinian Theory